The urban creative factory-creative ecosystems and (im)material design practices - Koutsari, Maria; Antonopoulou, Elena; Chondros, Christos (Interstices: Journal of Architecture and Related Arts, 2019)
Post-Fordism, with its evolution towards immaterial production in the areas of information, knowledge and affective, creative commerce, foregrounds design as a central, enabling activity. If this enablement finds particular application in cities of the Global North, it testifies to a shift in the geopolitical distribution of productive agency and application of international labour, one that sees industrial activities ‘reassigned’ to the Global South, leaving cities of the variably de-industrialised countries to develop cultural, symbolic, and creative economies.This paper examines the nature of urban place and the work regimes practised there consequent to these economies. It argues firstly for ‘cityness’ in these context to be understood as a creative urban factory – a place where older managerial and organisational techniques applied to factory environments in the service of high productivity are recalibrated and diffused across the entirety of urban territories. Secondly, the paper links the productivity of the creative urban factory with a biopolitical makeover of cities themselves, seeing in an optimisation of productive capacity a situation where the entirety of living labour is taken up and commoditised via the production of ever-customised lifestyles and identities. A raft of new identifying subject and worker categories emerge that exceed or elude the older class identifications, and with it, a certain potential to collectively counter the exploitation inherent post-Fordist work. While exploring the possibility of new identifying collectives – what Hardt and Negri have referred to as the multitude – the paper makes an argument for design itself to be a key medium for rethinking and re-enacting collective agency.As the harbinger of new forms of user participation and co-operative processes that are, by way of emerging technological tools, open, evolving, ad hoc, reflexive and customisable, design practice increasingly must contend and adapt to forms of de-professionalisation. Rather than seeing in this adaption a demise in profession position, the new possibilities appearing in design point to a low-tech, yet digitally-driven enabled, re-politicisation of design and creativity, one better able to contend with the strictures of the urban creative factory.